The importance of anthropological genetics research in Honduras, Central America - Baldi Salas, Norberto Francisco (2024)
With its unique geographic location at the northern end of the Central American isth- mus, Honduras straddles the boundaries of two distinct cultural regions—the Meso- american and the Istmo-Colombian. In this context, we briefly discuss the progress of population genetics studies conducted within Honduras. The text underscores the importance of conducting fieldwork to improve our under- standing of the genetic history, population dynamics, and emergence of diseases among the Indigenous communities of this country. Among the seven distinct In- digenous populations currently under genetic investigation, we highlight the case of the Garifuna people. We explore their origins, patterns of migration, genetic dif- ferentiation, and the prevalence of Hypertrophic Cardiomyopathy (HCM), which may be linked to founder effects. Our research endeavors in Honduras emphasize the value of an interdisciplinary approach in the study of local human populations that have been instrumental in shaping our evolving comprehension of the genetic landscapes within this unique geographical and cultural setting.